2014
DOI: 10.15282/jmes.7.2014.14.0112
|View full text |Cite
|
Sign up to set email alerts
|

Study on Performance of 80 Watt Floating Photovoltaic Panel

Abstract: Photovoltaicpanels are used to generate electric power. The surface temperature of the photovoltaic (PV) panels will affect theirefficiency,where the increment of temperature will decreasetheir efficiency and total power gain. In this study, we will discuss the performance of an 80 W floating photovoltaic (PV) panel in a pond simulator, whereby in a two hour experiment it shows up to 15.5% increment of energy gain compared to a normal photovoltaic (PV) panel. The floating photovoltaic (FPV) panel was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…However, as the cost of PV modules themselves have dropped a low-tilt angle system enables closer packing of modules (e.g., higher power per unit area) and can increase the solar electricity generated per unit area at an airport. In addition, for airports with surface water, floating solar PV farms [15][16][17][18][19][20][21] and even aquavoltaics [22] would enable an increased area for PV, as well as possibly reducing water surface glare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the cost of PV modules themselves have dropped a low-tilt angle system enables closer packing of modules (e.g., higher power per unit area) and can increase the solar electricity generated per unit area at an airport. In addition, for airports with surface water, floating solar PV farms [15][16][17][18][19][20][21] and even aquavoltaics [22] would enable an increased area for PV, as well as possibly reducing water surface glare.…”
Section: Resultsmentioning
confidence: 99%
“…Much of this need can be met via rooftop PV or the relatively immature building-integrated PV (BIPV) market [5][6][7][8][9][10]. The remainder will need to be met by large-area solar PV farms on either land-based solar PV farms [11][12][13][14] or even water-based floating solar PV farms [15][16][17][18][19][20][21][22]. However, as the global population increases 1.15% per year [23], attractive land and even waterways will become more valuable, especially in densely populated areas.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these parameters are air-motor speed (ω), air pressure (pAir), and electrical energy generated by the generator (P) on the loading. By knowing these characteristics, it will be easier to operate the system, such as knowing how much pressure is required and the speed to be achieved to achieve specific power or to achieve the maximum power transfer [23][24][25]. To be able to know the characteristics of the SS-CAES system, it can be done by entering the variable value of speed and pressure on the mathematical equations from the system that has been created.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we review some of them: Kaldellis and Kokala [5] investigated an experimental analysis was conducted in the laboratory soft energy application and environmental protection (SELAB) to determine the effect of pollution on the energy performance of PV-panels quantitatively. Majid et al [6] showed that the efficiency of PV cell decrease 0.485% per 1°C, after the surface temperature increase than 25°C. Elhab B. R. et al [7] presented a mathematical approach to determine optimum tilt angles for solar collector.…”
Section: Introductionmentioning
confidence: 99%